Bioactive Cellulose Nanocrystal-Poly(ε-Caprolactone) Nanocomposites for Bone Tissue Engineering Applications - Hong, Jung Ki; Cooke, Shelley L.; Whittington, Abby R.; Roman, Maren (Frontiers in Bioengineering and Biotechnology, 2021)
3D-printed bone scaffolds hold great promise for the individualized treatment of critical-size bone defects. Among the resorbable polymers available for use as 3D-printable scaffold materials, poly(ε-caprolactone) (PCL) has many benefits. However, its relatively low stiffness and lack of bioactivity limit its use in load-bearing bone scaffolds. This study tests the hypothesis that surface-oxidized cellulose nanocrystals (SO-CNCs), decorated with carboxyl groups, can act as multi-functional scaffold additives that 1) improve the mechanical properties of PCL and 2) induce biomineral formation upon PCL resorption. To this end, an in vitro biomineralization study was performed to assess the ability of SO-CNCs to induce the formation of calcium phosphate minerals. In addition, PCL nanocomposites containing different amounts of SO-CNCs (1, 2, 3, 5, and 10 wt%) were prepared using melt compounding extrusion and characterized in terms of Young’s modulus, ultimate tensile strength, crystallinity, thermal transitions, and water contact angle. Neither sulfuric acid-hydrolyzed CNCs (SH-CNCs) nor SO-CNCs were toxic to MC3T3 preosteoblasts during a 24 h exposure at concentrations ranging from 0.25 to 3.0 mg/mL. SO-CNCs were more effective at inducing mineral formation than SH-CNCs in simulated body fluid (1x). An SO-CNC content of 10 wt% in the PCL matrix caused a more than two-fold increase in Young’s modulus (stiffness) and a more than 60% increase in ultimate tensile strength. The matrix glass transition and melting temperatures were not affected by the SO-CNCs but the crystallization temperature increased by about 5.5 °C upon addition of 10 wt% SO-CNCs, the matrix crystallinity decreased from about 43% to about 40%, and the water contact angle decreased from 87 to 82.6°. The abilities of SO-CNCs to induce calcium phosphate mineral formation and increase the Young’s modulus of PCL render them attractive for applications as multi-functional nanoscale additives in PCL-based bone scaffolds.